A potential role of nanophytocompounds in diabetic foot ulcers - Thapa, Komal; Kanojia, Neha; Verma, Nitin (Trends in Immunotherapy, 2024)
Diabetes mellitus (DM) is characterized by hyperglycemia, which is a common endocrine disease. DM and its complications may lead to diabetic foot ulcers (DFU). DFU is associated with reduced wound healing because of altered cellular and cytokine responses, inadequate vascularization, infection, and neuropathy. One novel and promising approach to treating diabetic wound healing is the administration of compounds based on nanotherapeutics, such as nanoparticles and nanoscaffolds. Plant extracts can be administered more successfully by using nanoscale delivery methods. Plant extracts and their related phytocompounds can be nanostructured to enhance their bioavailability, regulate their release via extended delivery techniques to the wound site, and increase their penetration to the deeper layers of the skin. All these benefits are critical for the healing process. This brief overview covers the most recent methods to develop phytomedicine nanotherapeutics for the treatment of diabetic wounds.